2005
DOI: 10.1002/j.1939-4640.2005.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Prostate‐Specific Expressed Recombinant Plasmids With High Transcriptional Activity of Prostate‐Specific Membrane Antigen (PSMA) Promoter/Enhancer

Abstract: To screen different combinations of prostate-specific membrane antigen (PSMA) promoter/enhancer with the strongest transcriptional activity in prostate-specific cells, we used PSMA regulatory elements to control specific expression of the target gene in gene therapy of prostate adenocarcinoma. PSMA promoter and enhancer DNA sequences were amplified from the LNCaP human prostate cancer cell line by polymerase chain reaction, then recombinant plasmids of the enhanced green fluorescent protein (EGFP: pEGFP-PSMA(P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Unlike other prostate‐specific proteins (PSA, PAP, probasin), PSMA expression is downregulated by androgen, 6 which makes it a more useful marker in the treatment of androgen‐independent prostate carcinoma. Our previous work confirmed that a single PSMA enhancer with a PSMA promoter has the strongest regulatory activity in PSMA‐positive cells when different controlling element combinations were evaluated 7 …”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Unlike other prostate‐specific proteins (PSA, PAP, probasin), PSMA expression is downregulated by androgen, 6 which makes it a more useful marker in the treatment of androgen‐independent prostate carcinoma. Our previous work confirmed that a single PSMA enhancer with a PSMA promoter has the strongest regulatory activity in PSMA‐positive cells when different controlling element combinations were evaluated 7 …”
Section: Introductionsupporting
confidence: 71%
“…Plasmid DNA was harvested from E. coli strain JM109 using a plasmid miniprep kit (Omega). For a reporter vector, the recombinant plasmids prostate‐specific membrane antigen enhancer/promoter ‐enhanced green fluorescent protein (pPSMA E/P ‐EGFP) and pPSMA E/P ‐UPRT were constructed and screened by our department; 7 while pEGFP‐N1 (Clontech, Mountain View, CA, USA) were used as a control plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…More important, our results serve as a proof of principle to deploy alternative PCa-specific promoters that can distinguish malignant and benign disease. Several genes are upregulated at the transcriptional level specifically in PCa, including Differential Display Code 3 (DD3/PCA3), prostate- specific membrane antigen, and a-methylacyl-CoA racemase (3234). Given the extensive track record of the TSTA method, it should be feasible to use the promoters of these genes to develop a parallel transcription-amplified imaging strategy to specifically image intraprostatic PCa foci and better guide treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The tandem structure of a single enhancer and a promoter exerts the strongest driving effect with a driving capability 53 times of that of the PSMA promoter alone. Importantly, EGFP and UPRT are only expressed in PSMA‐expressing LNCaP cells (Zeng et al, 2005). These results not only proved the cell‐specific driving capabilities of PSMAe/p but also laid a solid foundation for targeted therapy of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%